1989
DOI: 10.1002/dev.420220208
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative relationship between nutritional effects on preweaning growth and behavioral development in mice

Abstract: Our objective was to establish whether nutritional effects on the behavioral development of preweaning mouse pups were linearly related to effects on body and brain growth or whether there was a threshold effect, with behavior being affected only by nutritional extremes. We also used a standardized scale of development to compare the relative magnitude of such effects on morphological and behavioral measures. The level of nutrient availability was manipulated continuously by rearing the pups in litter sizes ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The inverse relation seen in the untreated groups reflects the effects of normal variation in litter size on growth. As such, it is consistent with the findings of a previous study in which we varied litter size systematically and measured brain and behavioral development (Wainwright, Pelkman, & Wahlsten, 1989). However, in the ethanol groups, litter size is an indication of the effects of ethanol on pup survival, where the number of surviving pups is an indication of the overall severity of the treatment, that is, the smaller the litter, the more drastic the effects of the ethanol treatment on the remaining pups in the litter in terms of behavioral development and brain weight.…”
Section: Discussion: Comparison Of the Findings From The Mixed Effectsupporting
confidence: 90%
“…The inverse relation seen in the untreated groups reflects the effects of normal variation in litter size on growth. As such, it is consistent with the findings of a previous study in which we varied litter size systematically and measured brain and behavioral development (Wainwright, Pelkman, & Wahlsten, 1989). However, in the ethanol groups, litter size is an indication of the effects of ethanol on pup survival, where the number of surviving pups is an indication of the overall severity of the treatment, that is, the smaller the litter, the more drastic the effects of the ethanol treatment on the remaining pups in the litter in terms of behavioral development and brain weight.…”
Section: Discussion: Comparison Of the Findings From The Mixed Effectsupporting
confidence: 90%
“…That is to say that litters with fewer pups will have pups that weigh more, on average, than litters with larger numbers of pups. Wainwright et al (1989) showed that for every additional pup in a litter, body growth was retarded by the equivalent of 1.28 days, brain weight by 0.44 days, and behavioral development by 0.07 days. Therefore, it is sug-gested that litters of equal size be used whenever possible.…”
Section: Nutritional Effects and Litter Sizementioning
confidence: 99%
“…To describe the developmental stage of a mouse embryo or fetus, its chronological age (E16, for example) is conventionally used. However, because the prenatal growth rate of individuals varies substantially depending strongly on embryonic genotype and maternal environment (Wahlsten and Wainwright, 1977), the chronological age is not perfectly related to brain development (Wainwright et al, 1989). Previous studies have found that prior to birth, the body weight of a mouse is a better indicator of morphological maturity than age (Wahlsten and Smith, 1989;Bulman-Fleming and Wahlsten, 1991) and that more consistent results can be obtained by comparing brains of mice at the same body weight (Wahlsten, 1987;Wahlsten, 1992, 1993).…”
Section: Viewing and Data Presentationmentioning
confidence: 99%